2017
DOI: 10.1002/2017gl072514
|View full text |Cite
|
Sign up to set email alerts
|

The sensitivity of West Antarctica to the submarine melting feedback

Abstract: We use an ice sheet model with realistic initial conditions to forecast how the Amundsen Sea sector of West Antarctica responds to recently observed rates of submarine melting. In these simulations, we isolate the effects of a positive feedback, driven by submarine melt in new ocean cavities flooded during retreat, by allowing the present climate, calving front and melting beneath existing ice shelves to persist over the 21st century. Even without additional forcing from changes in climate, ice shelf collapse,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
109
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(123 citation statements)
references
References 54 publications
(106 reference statements)
12
109
2
Order By: Relevance
“…The lack of grounding line retreat (which would lead to additional VAF loss) may be because the nature of the experiments precludes melt under newly floating ice; other modeling studies (Arthern & Williams, 2017;Seroussi et al, 2017) suggest that melting of newly exposed shelf near the grounding line has a large impact on retreat. Still, the additional mass loss, ∼3 km 3 /a, is not large relative to the ∼21 km 3 /a currently being lost from the region.…”
Section: Discussionmentioning
confidence: 98%
“…The lack of grounding line retreat (which would lead to additional VAF loss) may be because the nature of the experiments precludes melt under newly floating ice; other modeling studies (Arthern & Williams, 2017;Seroussi et al, 2017) suggest that melting of newly exposed shelf near the grounding line has a large impact on retreat. Still, the additional mass loss, ∼3 km 3 /a, is not large relative to the ∼21 km 3 /a currently being lost from the region.…”
Section: Discussionmentioning
confidence: 98%
“…Numerous modeling studies have demonstrated that ice shelf basal melting is a critical factor in driving ice sheet retreat (e.g. Arthern & Williams, ; Cornford et al, ; DeConto & Pollard, ; Favier et al, ; Goldberg et al, ; Joughin et al, ), with basal melting near the grounding zone and in the new sub‐ice shelf cavities created as melting ice shelves go afloat being particularly important (Arthern & Williams, ; Reese et al, ; R. T. Walker et al, ). Thus, realistic representations of the magnitude and distribution of ice shelf basal melting in global climate models is essential for forecasting 21st century sea level rise.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous modeling studies have demonstrated that ice shelf basal melting is a critical factor in driving ice sheet retreat (e.g. Arthern & Williams, 2017;Cornford et al, 2015;DeConto & Pollard, 2016;Favier et al, 2014;Goldberg et al, 2019;Joughin et al, 2014), with basal melting near the grounding zone and in the new sub-ice shelf cavities created as melting ice shelves go afloat being particularly important (Arthern & Williams, 2017;Reese et al, 2018;R. T. Walker et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…We chose to use a model domain that follows the present‐day boundaries of Thwaites Glacier to keep model cost low enough to allow simulation of many ensemble members. However, previous studies have shown that the boundaries of Thwaites Glacier are likely to expand significantly in the future due to interactions with neighboring basins, particularly Pine Island Glacier (Arthern & Williams, ; Cornford et al, ). While ignoring this effect will affect the projections of total mass loss from the model, we expect it to have a secondary effect on quantifying the impacts of including or excluding ocean variability.…”
Section: Comparison To Other Studies Of Ice‐sheet Response To Climatementioning
confidence: 99%